Development and inâ€vitro evaluation of colon specific satranidazole tablet for the treatment of amoebiasis - Jagtap, Jitendra; Patil, Moreshwar; Patil, Vijay (Asian Journal of Pharmaceutics (AJP), 2014)
The delivery of drugs to the colon through oral route is valuable in treating diseases of the colon with the expectation to protect the drug during the transit time in the gastrointestinal tract and to allow its release only in the colon. The objective of this study was to develop colon targeted drug delivery system for satranidazole that is used in the treatment of amoebiasis. Matrix tablets containing a combination of guar gum and hydroxypropyl methyl cellulose (HPMC) K4M in different ratios were prepared by wet granulation technique followed by enteric coating with Eudragit S100. Citric acid was also added, which might further facilitate drug dissolution and absorption. All formulations were evaluated for hardness, swelling, drug content and inâ€vitro drug release studies. The results of the studies showed that colon targeted matrix tablet of satranidazole containing guar gum and HPMC K4M in the ratio proportion of 3:1 does not released drug in 0.1N HCl (pH 1.2) and small intestine (phosphate buffer, pH 7.4). When the dissolution study was continued in colonic fluids (phosphate buffer, pH 6.8), the matrix tablets released 79.21% drug while in the presence of 4% rat cecal content,it was 94.08% at the end of the 24 h. It was expected that guar gum could be degraded by colonic microflora containing anaerobic microorganism and the release may be controlled by HPMC K4M and citric acid. Studies demonstrated that orally administered Satranidazole matrix tablets can be used effectively for the delivery of the drug to the colon.